The relationship between third year students' concept of nursing and their clinical performace - Cortina, Grace F.
Nursing is most of the time used synonymously with service and caring. As such, nursing students -- third year students in this study -- are expected to at least have a concrete and well-defined concept of nursing, defined in this study as being the role of the nurse. The researchers assumed that a student who knows his or her role as a nurse will perform well in clinical as reflected by their grades in a nursing subject.